Multicultural and multidisciplinary Islamic religious education and its significance for nurturing religious moderatism - Waston; Suwartini, Sri (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2022)
In the last decade, Islamic Religious Education (IRE) has received a negative image because it is associated with the growth of religious radicalism. Thus, the demands for applying religious moderation in IRE are getting stronger. This study aimed to find epistemological models that can direct IRE to align with religious moderation. Efforts to find answers were carried out by studying the thoughts of several figures of Islamic philosophy and contemporary Islamic studies, pursued by qualitative studies, supported by case studies, and enriched by surveys. The results showed that Musa Asy'arie's Multidimensional Concept, Amin Abdullah's Multidisciplinary-Interdisciplinary-Transdisciplinary Concept, and Siswanto Masruri's Science Collaboration Concept could serve as epistemological footholds in building a multicultural IRE that lead to religious moderation.